Education through sport: prevention of social passivity of children and youth - Tamarskaya N.V.; Seryakova S.B.; Stremilova O.V.; Savelev G.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to ascertain the perspectives of leaders in organizations, instructors in physical education and sports (PE and sports), regarding the potential of this field in shaping the character and fostering the social engagement of children and young people. Methods and structure of the study. The research approach involved examining the outcomes of surveys conducted among administrators and instructors in the field of physical education and sports. The survey encompassed various aspects, including evaluating the potential of physical education and sports in shaping the development of children and young people, as well as assessing the preparedness of physical education and sports instructors to tackle educational challenges. The study involved 81 principals of educational institutions in the field of physical education and sports, as well as 91 physical education and sports instructors. Results and conclusions. The findings indicated that both the leaders in the field of physical education and sports and educators in general recognize the significance of harnessing the potential of this field to educate children and young people, fostering their pro-social engagement. However, they may not always be able to clearly articulate effective solutions to this issue.